Perancangan Sistem Informasi Berbasis Web untuk Layanan Pelanggan Di Segitiga Bermuda Café Coffee & Eatery Menggunakan Metode Waterfall - Ramadhani Airmas Sahid, Rubby; Hasna Nabila, Haula; Prastya, Indra; Saprudin (CV. Shofanah Media Berkah, 2024)
This research aims to design and implement an effective web-based information system to enhance customer experience and operational efficiency at Bermuda Triangle Cafe Coffee & Eatery. The research methodology includes interviews with cafe owners and customers, direct observation at the cafe, and literature review to support the development of the web-based information system. The findings indicate that implementing a web-based information system can improve customer information access, expand customer interaction, and enhance operational efficiency. The research contributes to the development of information technology in the food and beverage industry, particularly in improving customer service and operational efficiency in cafes.